Cognitive Semantics of Onomastics in the Field of Modern Linguistics (Zien Journal of Social Sciences and Humanities, 2022)
The Article Is Devoted To The Investigation Of Onomastic Problems Of Phraseological Units With Proper Nouns. Moreover, The Article Describes Some Proper Names Function In Phraseological Units With Semantic Characteristics And Component.